Perceived Intensity and Discrimination Ability for Lingual Electrotactile Stimulation Depends on Location and Orientation of Electrodes - Moritz Jr., Joel; Turk, Philip; Williams, John D.; Stone-Roy, Leslie M. (Frontiers in Human Neuroscience, 2017)
Malfunctioning sensory systems can severely impact quality of life and repair is not always possible. One solution, called sensory substitution, is to use another sensory system to bring lost information to the brain. This approach often involves the use of bioengineered devices that electrically stimulate somatosensory fibers. Interestingly, the tongue is an ideal location for electrotactile stimulation due to its dense innervation, moisture, and protected environment. Success with transmitting visual and vestibular information through the tongue indicates promise for future applications. However, sensitivity and discrimination ability varies between individuals and across the tongue surface complicating efforts to produce reliable and consistent sensations. The goals of the present study were to investigate these differences more precisely to better understand the mechanosensory innervation of the tongue so that future electrotactile devices can be designed more effectively. Specifically, we tested whether stimulation of certain regions of the tongue consistently result in better perception, whether the spacing of stimulating electrodes affects perceived intensity, and whether the orientation of electrodes affects perceived intensity and discrimination. To test these hypotheses, we built a custom tongue stimulation device, recruited 25 participants, and collected perceived intensity and discrimination data. We then subjected the data to thorough statistical analyses. Consistent with previous studies, we found that stimulation of the anterior medial tongue region was perceived as more intense than stimulation of lateral and posterior regions. This region also had the best discrimination ability for electrodes. Dividing the stimulated tongue area into 16 distinct regions allowed us to compare perception ability between anterior and posterior regions, medial and lateral regions, and the left and right sides of the tongue. Stimulation of the most anterior and medial tongue resulted in the highest perceived intensity and the best discrimination ability. Most individuals were able to perceive and discriminate electrotactile stimulation better on one side of the tongue, and orientation of stimulating electrodes affected perception. In conclusion, the present studies reveal new information about the somatosensory innervation of the tongue and will assist the design of future electrotactile tongue stimulation devices that will help provide sensory information to people with damaged sensory systems.